Silencing of the GluN1-NMDA Glutamate Receptor Subunit by Intranasal siRNA Increases the Latency Time for Seizures in the Pilocarpine Rodent Model of Epilepsy - Raphaela Gonçalves Barros Perri; Anieli Gaverio Mantello; Daiane Santos Rosa; Renê Oliveira Beleboni (MDPI AG, 2022)
Temporal lobe epilepsy (TLE) is the most prevalent and treatment-refractory type of epilepsy. Among the different mechanisms associated with epileptogenesis, overstimulation of glutamatergic neurotransmission has been associated with the onset and progression of seizures in TLE. Experimental evidence indicates that blocking the N-methyl-D-aspartate (NMDA) receptor or suppressing the expression of its subunit, mainly GluN1, may be effective in preventing epileptic seizures. Small interfering RNA (siRNA) has received attention as a potential therapeutic tool due to the inhibition of gene expression in some diseases. The present work evaluated the potential silencing effect of intranasal administration of an siRNA conjugate against the GluN1 subunit in animals submitted to the pilocarpine model of epilepsy. The results showed that the siRNA conjugate transfection system silences the GluN1 subunit in the hippocampus of rats when administered intranasally. As demonstrated by the RT-qPCR and Western blotting approaches, the silencing of GluN1 was specific for this subunit without affecting the amount of mRNA for other subunits. Silencing increased the latency time for the first tonic-clonic seizure when compared to controls. The overlapping of findings and the validation of the intranasal route as a pharmacological route of siRNA targeting the GluN1 subunit give the work a significant biotechnological interest.